PERAN BRAND AWARENESS MEMEDIASI PENGARUH DAYA TARIK IKLAN TERHADAP NIAT BELI BLIBLI.COM DI KOTA DENPASAR - Yuda, Ida Bagus Raka Wira; Giantari, I Gusti Ayu Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
This study aims to explain the role of brand awareness in mediating the effect of advertising attractiveness on purchase intention at Blibli.com in Denpasar City. This research was conducted in Denpasar City with a total sample taken of 120 respondents. The sample was determined using a nonprobability sampling model with a purposive sampling technique. The data analysis technique used is the classical assumption test, path analysis and Sobel test. The results of this study indicate that all hypotheses are accepted. Advertising attractiveness has a positive and significant effect on purchase intention, advertising attractiveness has a positive and significant effect on brand awareness, brand awareness has a positive effect on purchase intention and brand awareness is able to partially mediate the influence of advertising attractiveness on purchase intention at Blibli.com in Denpasar City. The implication of this research is that Blibli.com needs to pay attention to the implementation of advertising strategies so as to strengthen brand awareness to create purchase intentions at Blibli.com in Denpasar City. Consumers who are aware of the Blibli.com brand in Denpasar City can create consumer curiosity and interest in the Blibli.com brand, which in turn leads to consumer purchase intentions at Blibli.com.